Vitamin C and Mineral Contents in Selected Leafy and non-Leafy Vegetables of Bangladesh - Islam, SK Nazrul; Chowdhury, Gowsia; Ara, Tajin Samse; Khan, Md Nazrul Islam; Huque, Saiful; Barua, Sagarmay; Hassan, Nasmul (Bangladesh Journal of Nutrition, 2010)
Bangladesh Journal of Nutrition Vol.17 2004 p.1-6